Interviewing survivors of near-lethal self-harm: a novel approach for investigating suicide amongst prisoners. - Marzano, L; Rivlin, A; Fazel, S; Hawton, K (2009)
In most countries, rates of suicide in prison are higher than those reported in the general population, and seemingly on the increase. Previous studies of factors contributing to suicide in prisons have largely been limited to analyses of the clinical and prison records of prisoners who have died by suicide. In this paper we reflect on the limitations of this approach. Drawing on illustrative case vignettes from ongoing research, we argue that interviewing survivors of near-fatal incidents of self-harm offers a potentially fruitful method to further our theoretical understanding of this growing problem, and inform relevant policy.